An Investigations of Sound Absorbance Properties of Weft Knitted Spacer Fabrics - (:unkn) unknown (INT INST ACOUSTICS & VIBRATION, 2015)
Nonwoven fabrics have been used for many years in different technical applications; they have particularly been used as isolation materials in vehicles in order to reduce the noise heard within them, and they. They have achieved great popularity due to low production cost and good absorbance. However, the fabrics produced by making use of the nonwoven technique have some disadvantages including low resistance, low abrasion strength, poor aesthetic appearance and thickness. In order to eliminate these disadvantages, recent studies have reported that knitted fabrics could be an alternative to nonwoven fabrics. Various studies have focused on the impact on sound absorbance that the thickness and surface structure of knitted fabrics have. In this study, a number of knitted spacer fabrics, which had five different connection angles, were manufactured by using a plain knitting machine. The sound transmission loss levels of the developed fabrics were tested and analysed by Bruel and Kjaer tube instruments. At the end of the examinations, the sound absorbance behaviors at different frequencies were demonstrated in graphics based on the type of knitting. It was determined in the study that three factors have a major impact on the sound absorbance behaviour; thickness of fabric, micro porosity between fabric surfaces and yarn linear density in the interconnection of the fabrics.
Keywords: TRANSMISSION LOSS; ELEMENT